A Neurolinguistic Account of Learning Barriers in Thinking Patterns: From the Perspective of Classroom Writing in English - Peng, Virginia (Glottodidactica, 2005)
Teaching English as a foreign language to students invariably encounters 3 learning barriers: (1) the barrier between the instructor and students; (2) the barrier between the textbook author and the student; and (3) the barrier between the instructor and the textbook author. These are explained by applying neurolinguistic theory currently available in neuroscience. To help students learn English, particularly regarding writing, the instructor faces challenges to overcome such barriers, because teaching any language to students of a different culture requires a great deal of adjustment of brain functions on all parties involved. This paper addresses one particular issue, adjustment of the thinking process, from a neurolinguistic point of view; it specifically presents classroom writings, by analyzing them, in order to propose a remedy. The data are papers from first year university students. The materials were collected through participant observation and from student homework. These data are analyzed. The results of the analysis of the data are discussed in detail. The author concludes that pathways to students' protomeanings in the brain must be formed, and that repetition of exercises by relying on students' brain functions of memory can enhance understanding , because in writing, there is a large gap between writing a paragraph and an essay, which can be narrowed by the brain functions of memory.